Problem Based Learning on the Student’s Narrative Writing - Putri Fadillah; Rini Fadhillah Putri; Siti Mayang Sari (Journal Neosantara Hybrid Learning, 2024)
The increasingly popular term 'problem-based learning' does not refer to any particular educational method. Many have different meanings depending on the design of the educational methods used and the skills of the teacher. Currently, English is not only a language that must be applied to certain fields, but English is a medium for conveying something both orally and in writing. In this paper explains about Writing Narrative Text. The explanation begins with the definition of writing and types of text. The problem that will be raised in this paper is how to write Narrative Text. Narrative Text is a type of text that must be understood how to write it and its generic structure, so that it becomes a good and correct written work.